Identification of miRNA-mediated gene regulatory networks in L-methionine exposure counteracts cocaine-conditioned place preference in mice - Wang, Yan; Yang, Lvyu; Zhou, Hansheng; Zhang, Kunlin; Zhao, Mei (Frontiers in Genetics, 2023)
Methionine has been proven to inhibit addictive behaviors of cocaine dependence. However, the mechanisms underlying how methionine use corresponds to drug-induced behaviors still remain unclear. We performed mRNA and miRNA high-throughput sequencing of the prefrontal cortex in a mouse model of cocaine CPP combined with L-methionine in order to identify L-methionine target miRNAs and genes that participate in the cocaine conditioned place preference (CPP). As a reason for the L-methionine inhibiting cocaine CPP behaviorally, sequencing data analysis showed that L-methionine reversely regulated genes and miRNAs affected by cocaine. Pathways associated with drug addiction only enriched in CS-down with MC-up genes targeted by DE-miRNAs including GABAergic synapse, Glutamatergic synapse, Circadian entrainment, Axon guidance and Calcium signaling pathway. Drug addiction associated network was formed of 22 DEGs including calcium channel (Cacna1c, Cacna1e, Cacna1g and Cacng8), ephrin receptor genes (Ephb6 and Epha8) and ryanodine receptor genes (Ryr1 and Ryr2). Calcium channel gene network were identified as a core gene network modulated by L-methionine in response to cocaine dependence. Moreover, it was predicted that Grin1 and Fosb presented in TF-miRNA-mRNA coregulation network with a high degree of interaction and interacted calcium channels. Thus, we demonstrated the efficacy of L-methionine in counteracting the effects of cocaine CPP and identified specific genes modulated by L-methionine in response to cocaine dependence.